Persepsi Masyarakat Tentang Kesehatan Lingkungan Sekitar Limbah Pabrik Tahu Sumber Mulya Di Kelurahan Kebun Tebeng Kecamatan Ratu Agung Kota Bengkulu - Mirna Yunita; Edwar Edwar (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2016)
The background of the establishment of factories to Know Sumber Mulya At Village Kebun Tebeng Bengkulu city in the middle of settlements on the health of the community. The purpose of this study was to determine the public perception of the health of the environment around the plant waste tebeng knows the Village Gardens District of the Great Queen City of Bengkulu. the research method used is quantitative descriptive, with a population of this study were 312 heads of the family of four RT-powered plant waste that is RT.2, RT.3, RT.4, RT.18, and samples were taken as many as 15% of the total head of the family or as many as 47 heads of family. The research results obtained the highest score of the variable public perception of environmental health around the sewage plant to know the source mulya is 102 and 63 lowest scores, the ratio between the average score - to the maximum score is 66.4%, the level of understanding of respondents on the public perception of the variables environmental health around the sewage plant to know the source mulya included in the Good category.